Return: group design project for pin-point landing demonstrator using drone technologies - Felicetti, Leonard; Ignatyev, Dmitry; Grustan-Gutierrez, Enric; Tsourdos, Antonios (Elsevier, 2024)
In a rapidly changing world, engineers must identify societal needs, solve problems with ingenuity, and create new knowledge. While conventional taught-based courses provide a solid foundation of knowledge, they often fall short in stimulating creative thinking, translating theoretical knowledge into real-world solutions, and fostering leadership and teamwork. This paper proposes a project-based learning course designed to solidify and amplify the technical knowledge gained in preceding taught-based modules while developing essential soft skills. The course covers various stages of designing a reusable launcher-like demonstrator, aiming to simulate take-of and pinpoint landing operations using drone technology. This involves identifying system requirements and designing both software and hardware components. Throughout the course, students enhance their ability to critically formulate, solve, and evaluate engineering problems. They gain and apply technical knowledge in all aspects of drone technology, including fight dynamics, control, navigation, guidance, situational awareness, and communication. Additionally, students explore key aspects of systems engineering practices, risk management, and time management. This paper details the problem design, course timeline, outcomes and key lessons learned from the course.
Keywords: 40 Engineering; 4010 Engineering Practice and Education; 4007 Control engineering, mechatronics and robotics; 4008 Electrical engineering; Pin-point landing; multidisciplinary project; Project-Based Learning; system engineering; launch vehicles; landers